2021
DOI: 10.3390/su13073746
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Impact of ESG Practices in Corporate Finance

Abstract: This study examines the relationship between environmental, social, and governance (ESG) factors and corporate financial performance. Specifically, we study various individual ESG categories, both ESG strengths and concerns, and aggregate ESG factor and their impact on corporate financial performance including profitability and financial risk. We find a positive effect of ESG factors on corporate profitability, and the effect is more pronounced for larger firms. Among different ESG categories, corporate govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(99 citation statements)
references
References 19 publications
11
83
1
4
Order By: Relevance
“…However, some studies have found that good ESG scores correlate with higher returns on the shares of respective companies, with a lower risk for companies with good credit ratings [45][46][47]. Sassen and co-authors conducted a study of 8752 European companies and identified that companies that increased their ESG scores had the potential to increase their company value, the vector showing that the impact of ESG on company risk tended to decrease at high ESG values [48].…”
mentioning
confidence: 99%
“…However, some studies have found that good ESG scores correlate with higher returns on the shares of respective companies, with a lower risk for companies with good credit ratings [45][46][47]. Sassen and co-authors conducted a study of 8752 European companies and identified that companies that increased their ESG scores had the potential to increase their company value, the vector showing that the impact of ESG on company risk tended to decrease at high ESG values [48].…”
mentioning
confidence: 99%
“…First, we examine how corporate ownership and equity funds are (involuntarily) responsible for investment in the firms that are deemed problematic with the ESG (Environment, Society and Governance) standards. While the literature has recognized that “ESG is being incorporated into other portfolio products, such as ETFs” in the last several years [ 20 ], and the scholarly literature has exclusively addressed the impact of ESG scores on the financial performance of ETFs, corporate profitability, and investment decision-making among others [ 21 , 22 ]. Our analysis differs from the existing studies in that we study the connectivity of corporate ownership and investment funds to non-ESG firms, rather than the impact of ESG standards.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in banks, only Environmental disclosure has been cited to have a positive impact on the performance of the underlying asset. However, for Social and Government aspects individually, a negative effect is observed [22,23]. This may be seen as a contradiction, as the previous paragraph referenced a different point of view on the individual effects of ESG factors, but these results can in fact coexist as: (a) in one case, the article is examining the connection between ESG and stock performance, whilst the other researches ESG and CFP; (b) these results illustrate the current developing nature of research on ESG, CSR-particularly their effects on underlying assets.…”
Section: Esg Effects On Cfpmentioning
confidence: 95%